2021
DOI: 10.1159/000510909
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Liver Resection versus Percutaneous Radiofrequency Ablation for Small Single Nodular Hepatocellular Carcinoma: Comparison of Treatment Outcomes

Abstract: <b><i>Background:</i></b> Treatment outcomes of laparoscopic liver resection (LLR) and percutaneous radiofrequency ablation (p-RFA) for small single hepatocellular carcinomas (HCCs) have not yet been fully compared. The aim of this study was to compare LLR and p-RFA as first-line treatment options in patients with single nodular HCCs ≤3 cm. <b><i>Methods:</i></b> From January 2014 to December 2016, a total of 566 patients with single nodular HCC ≤3 cm treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 35 publications
4
45
0
Order By: Relevance
“…Even in recent clinical trials that compared the therapeutic efficacy of RFA with that of other treatment modalities, the reported 2-year cumulative incidence of LTP after performance of RFA with the conventional tumor puncture method ranged from 11% to 16.1% (5)(6)(7). This is higher than the typically lower than 3% LTP rate after hepatic resection (8,9).…”
mentioning
confidence: 92%
“…Even in recent clinical trials that compared the therapeutic efficacy of RFA with that of other treatment modalities, the reported 2-year cumulative incidence of LTP after performance of RFA with the conventional tumor puncture method ranged from 11% to 16.1% (5)(6)(7). This is higher than the typically lower than 3% LTP rate after hepatic resection (8,9).…”
mentioning
confidence: 92%
“…However, although RFA is widely accepted as an effective treatment option for small HCCs in nonsurgical candidates, it has a significantly higher rate of local tumor progression (LTP) compared to surgical resection, limiting its use in patients with resectable HCCs [ 4 5 6 7 ]. Several studies have demonstrated that there are no significant differences in long-term therapeutic outcomes between RFA and surgery, albeit with high LTP in RFA [ 6 8 9 ]. However, in patients with LTP, the required number of interventional procedures for controlling recurrent tumors was significantly higher than that in patients without LTP to obtain a similar overall survival outcome [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Non-subcapsular and non-perivascular tumors or tumors located in posterosuperior liver portions showed similar local tumor progression rates between RFA and laparoscopic surgical resection. 10 Although the present study did not investigate the association of the tumor location and the recurrence, the authors demonstrated that recurrence-free survival was comparable for HCC ≤2cm. Surgical resection provides better recurrence-free survival and comparable overall survival; however, it is accompanied by higher postoperative morbidity and longer hospital stay.…”
mentioning
confidence: 60%